Contribution to seismic safety & risk assessment of pre-code masonry buildings - Bernardo, Vasco Miguel Serrano (2022)
Through the centuries, earthquakes represent one of the main causes of damage and losses of cultural heritage, both monumental buildings and historic centers, affecting the development of many countries around the world. The Portuguese housing stock consists of several building typologies, some of which present a poor seismic performance like the masonry buildings built before the enforcement of the first seismic code (RSCCS) in 1958, only designed to withstand gravity loads. The research carried out in this thesis aims to contribute to the seismic safety and risk assessment of existing masonry buildings in Portugal. For this purpose, the seismic performance of these constructions is characterized through fragility and vulnerability curves, and tools are also made available to support the technical community regarding the seismic safety assessment of existing masonry buildings. The first part of the thesis (Chapter 2) is devoted to the historical appraisal review of pre-code masonry buildings, providing a detailed description of their main structural features. Subsequently (Chapter 3), a review of the literature on the seismic behavior of masonry buildings is presented, and the basic concepts for the seismic vulnerability and risk assessment based on probabilistic analysis are introduced. Then, a case study is conducted in Chapter 4 regarding the seismic vulnerability assessment of an aggregate of pre-code masonry buildings, in order to explore different modelling strategies and discuss the interaction between adjacent buildings in their seismic behavior and the need for intervention. Chapter 5 focuses in a comprehensive survey on the geometry of masonry buildings built until 1960, and the respective statistical treatment, allowing to define representative archetypes of the building stock. Chapter 6 employs the above statistical information, together with the variability of material properties, to generate a large synthetic database of representative masonry buildings, consisting of 18.000 structures up to five stories high. Based on non-linear static analyses performed on the entire database, the influence of geometry on the seismic behavior of structures is discussed and the uncertainty in their capacity is quantified. Furthermore, seismic fragility curves are derived, and mechanistic vulnerability functions are provided, which can be used in seismic risk/loss studies or for a code-based seismic assessment. Based on the above results, the seismic risk (Chapter 7) of masonry buildings in the Metropolitan Area of Lisbon (MAL) is evaluated using probabilistic methods and considering different states of conservation/degradation of the structures. Finally, in Chapter 8, novel and expeditious methods are derived through reliability-based analyses for seismic assessment of the masonry buildings in all Portuguese territory. The proposed methods are calibrated with the seismic safety assessment procedures preconized within part 3 of Eurocode 8 (EC8-3) to be easily applied by the technical community.